Analisis Kecepatan MySQL dan PostgreSQL pada Windows 11 dan Kali Linux 2022 - Rosari, Happy Sandhiyadini; Hakim, Muhammad Syaibani Al; Sibagariang, Efifania; Kardian, Aqwam Rosadi (STIKOM Tunas Bangsa Pematangsiantar, 2023)
In the era of the industrial revolution 4.0 now, the use of the internet is developing progressively and slowly digitalization arises in every corner of human life. One of them is digital database management on computer systems and the internet, either within a group, institution, or between individuals. With the development of science, there are more variations and types of database systems that can be used based on the needs of their use. There are several factors that can be used as reasons for choosing a database system, one of them is access speed such as to respond to queries sent to the server. In this study, a comparison analysis of the speed of the MySQL and PostgreSQL database systems was carried out for the SELECT, UPDATE and DELETE commands on data with a maximum number of 1.000,000 rows of data. Testing is performed on Windows 11 and Kali Linux 2022 operating systems. The results of this study found that 5 out of 6 query execution trials ran faster on the Kali Linux 2022 operating system.